Dopaminergic synapses in the caudate of subjects with schizophrenia: Relationship to treatment response - Roberts, Rosalinda C.; Roche, Joy K.; Conley, Robert R.; Lahti, Adrienne C. (Synapse (New York, N.Y.), 2009)
The typical symptoms of schizophrenia (SZ) are psychotic symptoms (hallucinations, delusions, disorders of thought or speech, grossly disorganized behavior) as well as cognitive impairments and negative symptoms. Not all patients respond to treatment and in those who do, only psychotic symptoms are usually improved. Imaging studies have shown that SZ subjects with high striatal dopamine release are far more responsive to antipsychotic drugs than those patients who have dopamine levels lower than or comparable to that of normal controls. In the present study we hypothesized that there was a link between psychosis and the number of dopaminergic synapses in the caudate nucleus in SZ. We examined dopaminergic synapses at the electron microscopic level in postmortem caudate from cases obtained from the Maryland Brain Collection. SZs were subdivided based on treatment response or resistance. The tissue was processed for the immunocytochemical localization of tyrosine hydroxylase (TH), the synthesizing enzyme for dopamine, and prepared for electron microscopy. The density of all TH labeled synapses was 43% greater in treatment responders than in controls and 62% greater in than in treatment resistant SZ. Axodendritic, but not axospinous, TH‐labeled synapses showed this increase. TH‐labeled axodendritic synapses in treatment responders were elevated in density (1.95 ± 0.093/10 μm3) compared to treatment resistant SZ (0.04 ± 0.017/10 μm3) and controls (0.11 ± 0.044/10 μm3). The results of the present study suggest that one anatomical underpinning of good treatment response may be a higher density of dopaminergic synapses and support a biological basis to treatment response and resistance. Moreover, these data have important implications for linking specific neuropathology with particular symptoms. Synapse 63:520–530, 2009. © 2009 Wiley‐Liss, Inc.